The effect of Google Earth Pro-assisted guided discovery learning on students' cognitive outcomes - Rachma Aulia Hasan; Alfi Sahrina; Ike Sari Astuti; Galuh Maulidiyahwarti (Universitas Pendidikan Indonesia, 2025)
Students' cognitive learning outcomes in Geography remain relatively low, as evidenced by the average class score, which has not yet met the Minimum Completion Criteria (KKM). This low learning outcome is influenced by the delivery of material that tends to be abstract without interactive media, making it difficult for students to understand spatial concepts. The Guided Discovery Learning model, supported by Google Earth Pro, is a solution because it allows students to explore geographic objects interactively and contextually, thereby stimulating active learning and fostering meaningful understanding. This study aims to analyze the effect of Guided Discovery Learning assisted by Google Earth Pro on students' cognitive learning outcomes. The method used is a quasi-experimental Post-test Only Control Group design across two classes: the experimental class and the control class, selected based on teacher recommendations. Data were collected through essay tests on cognitive learning outcomes in accordance with the learning objectives. The results of the study indicate a significant effect of the model, as evidenced by the post-test scores of the experimental class being higher than those of the control class. The Stimulation stage in Guided Discovery Learning is a research finding that influences learning outcomes by creating an interactive, contextual, and meaningful learning experience. Abstrak Hasil belajar kognitif murid pada mata pelajaran Geografi masih tergolong rendah, terlihat dari rata-rata nilai kelas yang belum memenuhi Kriteria Ketuntasan Minimal (KKM). Rendahnya hasil belajar ini dipengaruhi oleh penyampaian materi yang cenderung abstrak tanpa media interaktif, sehingga murid kesulitan memahami konsep spasial. Model Guided Discovery Learning berbantuan Google Earth Pro hadir sebagai solusi, karena memungkinkan murid mengeksplorasi objek geografi secara interaktif dan kontekstual, sehingga merangsang keaktifan belajar dan meningkatkan pemahaman bermakna. Penelitian ini bertujuan menganalisis pengaruh Guided Discovery Learning berbantuan Google Earth Pro terhadap hasil belajar kognitif murid. Metode yang digunakan adalah eksperimen semu (Quasi Experimental) dengan desain Post-test Only Control Group pada dua kelas, yaitu kelas eksperimen dan kelas kontrol yang dipilih berdasarkan rekomendasi guru. Data dikumpulkan melalui tes esai hasil belajar kognitif sesuai dengan tujuan pembelajaran. Hasil penelitian menunjukkan adanya pengaruh signifikan penggunaan model tersebut, dibuktikan dengan nilai post-test kelas eksperimen yang lebih unggul dibandingkan kelas kontrol. Tahap Stimulation dalam Guided Discovery Learning menjadi temuan penelitian yang mempengaruhi hasil belajar karena menciptakan pengalaman belajar interaktif, kontekstual, dan bermakna. Kata Kunci: Google Earth Pro; guided discovery learning; hasil belajar kognitif